Chicken Little and the Big Bad Wolf - Wedelich, Sam (Scholastic Press, 2021)
When Chicken Little runs into the Big Bad Wolf (literally), her first instinct is to fly, like the other chickens, but she decides to investigate instead--and finds that this particular wolf is not interested in eating chickens, he is just looking for a place to call home.